Chloroplast genomic diversity in eleven Pennisetum species - He, Muhan; Wang, Qi; Zhang, Yuwen; Shi, Chunjuan (Frontiers in Genetics, 2026)
BackgroundThis study presents a comprehensive analysis of the chloroplast genomes from eleven Pennisetum species, including major and minor millets. Through sequencing and assembly, we characterized the chloroplast genomes, revealing conserved gene content and structure while also identifying species-specific variations and mutational biases that suggest adaptive evolutionary processes.ResultsOur findings demonstrate a general preference for A/T-ending codons in line with the AT-rich nature of chloroplast DNA, as evidenced by Relative Synonymous Codon Usage analysis, which indicates codon usage bias and hints at evolutionary pressures for translational efficiency. Intron analysis within these genomes unveiled considerable variability, reflecting the genomes’ evolutionary flexibility and potential for adaptation to diverse environmental conditions. Comparative genomic analyses elucidated the phylogenetic relationships among the Pennisetum species, aligning with known taxonomic classifications and uncovering new evolutionary insights. Additionally, the study identified numerous simple sequence repeats, providing valuable markers for further genetic and phylogenetic research.ConclusionOverall, this research enhances our understanding of chloroplast genome evolution in Pennisetum, providing a valuable genetic resource that contributes to botanical and agricultural knowledge while underscoring the broader significance of plastome studies in elucidating plant evolutionary mechanisms.